Counseling and Training on The Application of Criminal Sanctions for Violations of BPJS Ketenagakerjaan - Sihombing, Ceria Cristy Kayani; Simanullang, Sanco; Pahlevi, Habieb; Riady, Yasir; Ajmal, Muhammad (Aktual: Jurnal Pengabdian Kepada Masyarakat, 2025)
Background of the study: Employment social security is a basic right of workers guaranteed by the state through BPJS Employment.Purpose and scope of the paper: This research analyzes the effectiveness of implementing criminal sanctions based on Article 55 of Law Number 24 of 2011 for violations of BPJS Employment obligationsMethods: This study uses a juridical-normative approach, which aims to analyze laws and regulations relevant to the problem of company compliance with BPJS Ketenagakerjaan's obligations.Results: The results of this research recommend strengthening regulations, digitizing supervision, and incentives for compliant companies to ensure effective and equitable implementation of social security.Conclusion: The employment social security system in Indonesia, especially those managed by BPJS Ketenagakerjaan, has an important role in protecting workers from social risks. The implementation of this system still faces many obstacles, especially the low level of corporate compliance.